The effect of overnight culture after thawing of D3 cleavage-stage embryos on clinical pregnancy outcomes: focus on embryo development to day 4 - Lan, Liuping; Li, Xiang; Luo, Bowen; Liu, Weiwu; Zhu, Lingling; Zhang, Juguang; Wen, Jian; Feng, Keng; Li, Derong; Lei, Feifei; Deng, Guosheng; Luo, Yudi; et al. (Frontiers in Endocrinology, 2025)
ObjectiveThis study aims to investigate the impact of day-3 (D3) cleavage-stage embryo thawing with immediate transfer versus thawing and overnight culture before transfer on clinical outcomes. It also examines the relationship between cleavage-stage embryo developmental speed after overnight culture and clinical pregnancy outcomes, as well as factors influencing clinical pregnancy in frozen embryo transfer (FET).MethodsA retrospective analysis was conducted on 1,040 patients who underwent D3 cleavage-stage frozen embryo transfer at Yulin City Maternal and Child Health Hospital between July 2022 and December 2023. Patients were divided into two groups based on embryo culture time after thawing: control (same-day transfer, 2-3 hours) and experimental (overnight culture, 18-20 hours). Clinical pregnancy rates, embryo implantation rates, early miscarriage rates, and multiple pregnancy rates were compared between groups. The experimental group was further subdivided based on the number of cleavage blastomeres increased after culture: A1 (≥4 blastomeres), A2 (1-3 blastomeres), and A3 (no increase). A binary logistic regression analysis identified independent factors affecting clinical pregnancy outcomes in FET.ResultsNo significant differences were found between the control and experimental groups in clinical pregnancy rate (37.2% vs. 40.2%), embryo implantation rate (24.9% vs. 26.4%), early miscarriage rate (13.1% vs. 18.8%), or multiple pregnancy rate (9.2% vs. 10.2%) (P > 0.05). In the experimental group, clinical pregnancy rates for A1, A2, and A3 subgroups were 44.2%, 29.8%, and 25.5%, respectively. Early miscarriage rates were 18.6%, 10.7%, and 38.5%, showing statistically significant differences (P < 0.05). Female age, endometrial thickness, embryo morphology, and the number of cleavage blastomeres were identified as independent factors influencing clinical pregnancy rate.ConclusionThis study indicates that D3 embryos with an increase in the number of blastomeres to more than four or entering the compaction stage after overnight culture have better pregnancy outcomes. Female age and endometrial thickness are important factors influencing clinical pregnancy rates. Optimizing culture conditions and ensuring optimal endometrial thickness may help improve the success rate of frozen-thawed embryo transfer.